Novel trends in cutaneous manifestations of geriatric dermatoses in a tertiary care hospital, South India: Latest trends in geriatric dermatosis - budeda, Hasini; B, Indira; S, Darsan; V. V. V. Satyanarayana; Purushothaman, Suruthi (Journal of Pakistan Association of Dermatologists, 2022)
Introduction: Geriatric dermatoses are one of the common presentations for elderly in day-to-day. According to 2011populatioand censes it is 8.6%. and is expected to come to 19% by 2050 due to increased life expectancy. This study aims to evaluate the spectrum of skin presentations in elderly population. Objective: To evaluate the prevalence of various geriatric dermatoses in patients attending DVL OP Of GGH, Kakinada METHODS: This is a cross-sectional observational study carried out on 395 consecutive patients aged 60 years and above between october2020 to march 2021 in Department of Dermatology of a Tertiary care hospital in East Godavari district. RESULTS: Out of 395 patients studied with male to female ratio of 1.3, mean age group is 60-65 years. Infections and Infestations (36%) were the most common followed by Physiological changes (26%%), eczema (14.65%%) Few cases which are rare, have been observed during the study. CONCLUSION: Geriatric dermatology is an emerging branch in dermatology, and an update on this, will go a long way to effectively manage these patients. From our study we found that infectious diseases followed by senile pruritus are the most common skin diseases among elderly patients.